The relationship between taxes and economic growth: evidence from Serbia and Croatia - Kalaš, Branimir; Mirović, Vera; Milenković, Nada (The European Journal of Applied Economics, 2018)
This study presents an empirical analysis of taxes and economic growthin Serbia and Croatia in the period 2007-2016. In order to identify theimpact of tax forms on economic growth and their relationship, theauthors decided to set up a panel regression where gross domesticproduct is the dependent variable, while corporate income tax, valueadded tax, social security contributions and excises are independentvariables. The results of random effect model have shown that corporateincome tax, value added tax and social security contributions have apositive impact on the gross domestic product, while excises affect thegross domestic product negatively. However, only value added tax hasa statistically significant impact on economic growth in these countries,with each increase in revenue from this tax contributing to the growthof gross domestic product in the observed period.